Intérêt de l’approche systémique pour l’étude de formations végétales en milieux forestiers : l’exemple de la Forêt de Fontainebleau - Micheline Hotyat (VertigO)
Forests are complex systems that have a large number of structures subjected to spatial and temporal variations. This complex landscape is marked by geological structure and soils but also by human activities. If these landscapes are well known today, even famous, it is important to understand how these various floristic entities are structured? What role have had the human activities past on the current constitution of plant cover? How to do the relative share between environmental conditions, biological data and multiple societal interventions to build dynamic patterns to help a better understanding of "anthropo-forestry-systems" to better understand their evolution and to manage them better.